Promoting a sharing economy in the Islamic finance industry: A study of selected OIC countries - Abdul Razak, Dzuljastri; Abdul Wahab, Abdul Hamid (2018)
Islamic finance has been in existence for the past centuries. Nonetheless, the realization of the real objectives of the industry is still a dream yet to be true. The goal of Islamic finance is to promote a sharing economy whereby money is not concentrated in the hands of a few individuals. This purpose of this study is to investigate the application of mudarbah and musharakah concepts which facilitate a sharing economy where profit and loss is shared between the bank and customer compared to debt financing that utilizes murabahah concept. The methodology is based on secondary data obtained from central banks of five selected OIC countries. The results indicated that Indonesia, Sudan and Bangladesh recorded the highest amounts in terms of mudarabah financing while Malaysia, Indonesia and Pakistan recorded the highest amounts in terms of musharakah financing. The results also indicated that murabahah financing is high in Malaysia, Bangladesh, Indonesia and Sudan. Pakistan registered the lowest amount in terms of murabahah financing.